(untitled) (Universal International Scientific Journal, 2026)
The digital transformation processes observed in the last decade — the introduction of artificial intelligence systems, algorithmic management, the platform economy, remote work formats, and the expansion of digital education ecosystems — are systematically reorganizing the structure and functional mechanisms of the labor market. These changes are not only updating the nomenclature of professions, but are also fundamentally transforming the psychological foundations of professional development. The modern work environment promotes flexibility over stability, and metacompetences over traditional competencies as a priority value [1. 42 p.].